The star packer - Bradbury, Robert N. (Robert North); Wayne, John, 1907-1979; Lone Star Productions (1933-1935); Cinetel Films ([Los Angeles, CA] : Lone Star Productions, 1934)
When he learns of a planned bank holdup in Little Rock, John Wayne organizes the people and sets a trap for the robbers
John Wayne, Varna Hillie, George Hayes, Yakima Canutt, Billy Franey, Earl Dwire, Tom Lingham.
Cinematographer, Archie Stout; editor, Carl Pierson.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Marshals -- West (U.S.) -- Drama; Gangsters -- West (U.S.) -- Drama; West (U.S.) -- Drama; Sheriffs -- West (U.S.) -- Drama; Gold mines and mining -- Drama; Western films; Feature films; Internet videos; Streaming video